Impact de l’immunothérapie dans la prise en charge du cancer du poumon « Etude rétrospective menée à l’Hôpital Militaire d’Instruction Mohammed V- Rabat » - ATBIB, Yassine; Essad, Ayoub; Zhar, Hajar; Tadlaoui, yasmina; AIT EL CADI, Mina; BOUSLIMAN, Yassir (Jour Med Resh and Health Sci, 2022)
Lung cancer is one of the most common cancers in the world, it usually occurs between the ages of 50 and 65. The main culprit being smoking, incriminated in nearly 9 out of 10 cases. There are two main types of bronchopulmonary cancers: small cell lung cancer (SCLC) which represents around 15 to 20% and non-small cell lung cancer (SCNLC) which represents the most frequent histological form with around 80 to 20%. 85% of all bronchial cancers. The determination of the histological type and the stage is important for the choice of the therapeutic strategy. For the management of bronchial cancer, a distinction is made between local treatments, precisely targeting the tumor (surgery, radiotherapy) and systemic treatments (chemotherapy, targeted therapies and immunotherapy). Immunotherapy, which has become a standard treatment for advanced or metastatic lung cancer, is based on the use of immunological checkpoint inhibitors. Anti-checkpoints are synthetic monoclonal antibodies that will allow them to reach their targets and block certain tumor resistance mechanisms. This is how we have seen the development of monoclonal or anti-PD-1/PD-L1 antibodies, currently a major target in the treatment of NSCLC. The objective of our retrospective observational study is to show the positive impact of immunotherapy in the management of lung cancer, and more specifically metastatic NSCLC, by reviewing the use of anti-PD- 1/PDL1 within the HMIMV between March 2019 and October 2021. To do this, we sought to describe the population having received immunotherapy comprising an anti-PD-1 or an anti-PD-L1 for the management of metastatic NSCLC, and to obtain survival data which will be compared. to those of a population treated with chemotherapy. The two immunotherapies in our study are pembrolizumab (anti-PD-1 antibody) and atezolizumab (anti-PD-L1 antibody). The most represented age group was 60 to 69 years old with a male predominance and a positive smoking status of 83%. The factors that motivated the consultation were mainly the association of respiratory signs and those of locoregional extension in patients with a respective frequency of 96% and 90%. All the patients included in our study had metastatic pathology, respecting the Marketing Authorization and the inclusion criteria. Adenocarcinoma was the most frequently diagnosed in the patients of our cohort, and therefore the form mainly found in this study. Tolerance was assessed, 90% of patients presented adverse effects with a grade ranging from 1 to 2, which confirms the good tolerance of immunotherapies. Nausea-vomiting, diarrhea and skin rash are the most common adverse events. The best progression-free survival rate was observed in the pembrolizumab group with a mean PFS of 7.6 months and a 95% CI of [6.8 – 8.3], the worst in the chemotherapy group with a mean PFS of 5.42 months and a 95% CI of [4.6 – 6.2]. The group treated with atezolizumab presents an intermediate PFS with a mean of 7 months and a 95% CI of [6.3 – 7.8]. It should be noted that the very small number of patients treated with atezolizumab made it impossible to produce a reliable curve. We sought to compare the PFS of the groups according to the tumor expression of the PD-L1 marker. There is no predictive value of benefit in terms of survival or objective response rate, regardless of the PD-L1 positivity threshold (?5% or ?5%). While this work has enabled us to take stock of the positive impact of immunotherapy in the management of lung cancer within our establishment, it nevertheless has certain limitations: the very small number of patients included in the study and the lack of information available in the patient record given the retrospective nature of the study.